Strategic IT governance and performance frameworks in large organizations - Maleh, Yassine, 1987- (Advances in business information systems and analytics (ABISA) book series., 2019)
"This book discusses the strategic information technology governance in large organizations. It also explores the strategic IT governance through new approaches: IT governance maturity in large organizations, IT agility, and information system security"--